Squamous cell carcinoma of the anterior two-third of tongue - K Umesh; B Vidya; Vishal Dhirajlal Modha; Sadaf Bin Manawar (Wolters Kluwer Medknow Publications, 2016)
Tongue is the most common site for oral squamous cell carcinoma. The various treatment options for carcinoma of anterior tongue are wide excision, hemiglossectomy and primary excisions along with elective neck dissection. Here we show report of a case of carcinoma of anterior tongue.